A New Active Antenna Unit for Portable Microwave Bio-Dosimeters - Andrey Simakov; Igor Vodokhlebov; Yuriy Voronov (Proceedings)
Today, the growing ecological contamination by microwave irradiation requires new devices and information systems to monitor dangerous situations, especially in big cities, and provide safety for the population. This work is focused on the design of anew antenna unit for advanced portable personal microwave dosimeters and irradiation monitoring systems.